The construction of permanent education in the process of health work in the state of Minas Gerais, Brazil - Kênia Lara Silva; Juliana Alves Viana Matos; Bruna Dias França (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To analyze the practices of Educação Permanente em Saúde (EPS - Permanent Education in Health) and its repercussions on the work process of the involved actors. Method: This is a qualitative study, developed in two phases: mapping of EPS experiments in Minas Gerais and visits and interviews with nine managers, 22 coordinators and 18 professionals from ten selected municipalities. The first phase occurred from March to October 2014 and the second from March to June 2015. The material was analyzed under the prism of Critical Discourse Analysis. Results: The denomination of educational actions as training still prevails among professionals, contrary to national politics. However, it was possible to identify EPS signs in the professionals' daily life, indicating changes in the work process. Conclusion: There is evidence of a process of transformation of educational practices mobilized by EPS, despite the hegemonic model of education in the field of health work. Implications for practice: This is the need to problematize the daily work process in health.